Propuesta de metodología de mantenimiento de clase mundial (MCM) en el área molinos del grupo FAMILIA en Planta Lasso - Lamingo Chingo, Cristian Paúl (2019)
For the proposal of World Class Maintenance in the first instance a comparative analysis of data was performed between the initial situation in which the maintenance of equipment was in past years, this was done by verifying the database which contained information from a history of maintenance of the machine MP5 - MP2, this is fundamental for the investigative work in which the next step was the implementation of the criticality matrix quantifying the values in a table and identifying the equipment if they are considered critical, important or predictable by performing it independently of each machine that information allows to plot the lost tree, then proceeded to perform the performance evaluation through the KPI's to calculate the availability in the area of mechanical maintenance mills and correct certain faults by transferring them to percentage tables and so on tar objective of the proposal that is to attack the most frequent and continuous damage to paper machines, causing unscheduled work stoppages that harm both economically and socially, affecting all parties involved, Finally, through the performance evaluation, it was possible to identify the effectiveness of the application of the technological proposal of a world class maintenance corroborating a continuous improvement in the maintenance process in such a way that the reduction of costs and unscheduled stops is achieved. with the purpose of increasing the efficiency and productivity of the equipment by guaranteeing and increasing the useful life of equipment and mechanical parts that make up the paper machine as a common result, continuous improvement and increased reliability are generated, generating higher net income on the other hand it also seeks to better manage the resources for each activity carried out and, above all, to determine the consequences of potential events in failures of the production systems within the operational context.